Knowledge and Attitude of Men on Contraception Methods - Silwal, Suvekshya; Neupane, Sujana (Journal of Karnali Academy of Health Sciences, 2018)
Family planning refers to a conscious effort by a couple to limit or space the number of children they have through the use of contraceptive methods. Family planning in the global health field often revolves around women and girls. It is often regarded as the woman's responsibility, but there is growing recognition of the need to involve men in family planning programs.One of the most serious problems of developing countries still have to solve is their rapid and uncontrolled increase in population. It is well documented that men’s general knowledge and attitudes concerning the ideal family size, gender preference of children, ideal spacing between child births, and contraceptive method use greatly influence women’s preferences and opinions. Family planning has traditionally been viewed as the woman's responsibility, but there has been a growing recognition of the need to involve men in family planning programs as a means of achieving reproductive health objectives, as well as attaining greater gender equity.